(untitled) (Heritage, 2026)
The pilgrimage travel writings of Grigorije Božović testify to their wide scope of reception. This paper will focus on a comparative examination of the literary and aesthetic strategies employed in the representation of churches and the constitution of sacred space, within an interdisciplinary framework encompassing art history, aesthetics, and literary studies. The corpus has been excerpted from a larger number of travel accounts contained in the book Na hadžiluku (On Pilgrimage), with particular emphasis on the travelogues , Kičevska Prečista” and , By the Swan Song of Rade Neimar”, which stand out as the most representative examples of the problem under consideration. Spatial theory will be established as an integrative theoretical framework linking the perspectives of art history and literary studies. The poetics of sacred space will enable an interpretation of churches in Božović’s travel writing from a dual perspective: as artistic and architectural objects, and as literary representations. The functional descriptions of churches, as well as the spiritual and symbolic dimension of the selected travel-reportage narratives, will be analyzed in their interrelation, through the lens of the constitution of sacred space, within the framework of a hierotopic and hierophanic approach.